2021
DOI: 10.3390/ijms221810112
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Metabolic Reprogramming during Wound-Induced Organ Formation in Tomato Hypocotyl Explants

Abstract: Plants have remarkable regenerative capacity, which allows them to survive tissue damage after exposure to biotic and abiotic stresses. Some of the key transcription factors and hormone crosstalk mechanisms involved in wound-induced organ regeneration have been extensively studied in the model plant Arabidopsis thaliana. However, little is known about the role of metabolism in wound-induced organ formation. Here, we performed detailed transcriptome analysis and used a targeted metabolomics approach to study de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…To investigate the hormonal regulation of wound-induced de novo organ formation in tomato hypocotyl explants, we performed targeted profiling of several phytohormonerelated metabolites on different regions of the hypocotyl and at different times after excision and found that endogenous levels of several hormones changed shortly after root and shoot excision. Cross-validation with previous RNA-seq data [9] allowed us to confirm that genes related to auxin and cytokinin (CK) crosstalk were dynamically regulated during de novo organ formation both in the apical and the basal region of the explants within a short developmental window, which contributed to the observed region-specific regenerative responses.…”
Section: Of 21mentioning
confidence: 71%
See 4 more Smart Citations
“…To investigate the hormonal regulation of wound-induced de novo organ formation in tomato hypocotyl explants, we performed targeted profiling of several phytohormonerelated metabolites on different regions of the hypocotyl and at different times after excision and found that endogenous levels of several hormones changed shortly after root and shoot excision. Cross-validation with previous RNA-seq data [9] allowed us to confirm that genes related to auxin and cytokinin (CK) crosstalk were dynamically regulated during de novo organ formation both in the apical and the basal region of the explants within a short developmental window, which contributed to the observed region-specific regenerative responses.…”
Section: Of 21mentioning
confidence: 71%
“…To enhance our understanding of de novo organ formation in plants, we established a new experimental system using 'Micro-Tom' hypocotyl explants after shoot and root excision, as these explants can regenerate the missing structures without the exogenous application of plant hormones [8,9]. We found that endogenous hormone levels were layered along the apical-basal axis of the hypocotyl before wounding (this work).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations